Development of a cross-sectoral antimicrobial resistance capability assessment framework. - Ferdinand AS; McEwan C; Lin C; Betham K; Kandan K; Tamolsaian G; Pugeva B; McKenzie J; Browning G; Gilkerson J; Coppo M; James R; et al. (BMJ Publishing Group, 2024)
Antimicrobial resistance (AMR) is an urgent and growing global health concern, and a clear understanding of existing capacities to address AMR, particularly in low-income and middle-income countries (LMICs), is needed to inform national priorities, investment targets and development activities. Across LMICs, there are limited data regarding existing mechanisms to address AMR, including national AMR policies, current infection prevention and antimicrobial prescribing practices, antimicrobial use in animals, and microbiological testing capacity for AMR. Despite the development of numerous individual tools designed to inform policy formulation and implementation or surveillance interventions to address AMR, there is an unmet need for easy-to-use instruments that together provide a detailed overview of AMR policy, practice and capacity. This paper describes the development of a framework comprising five assessment tools which provide a detailed assessment of country capacity to address AMR within both the human and animal health sectors. The framework is flexible to meet the needs of implementers, as tools can be used separately to assess the capacity of individual institutions or as a whole to align priority-setting and capacity-building with AMR National Action Plans (NAPs) or national policies. Development of the tools was conducted by a multidisciplinary team across three phases: (1) review of existing tools; (2) adaptation of existing tools; and (3) piloting, refinement and finalisation. The framework may be best used by projects which aim to build capacity and foster cross-sectoral collaborations towards the surveillance of AMR, and by LMICs wishing to conduct their own assessments to better understand capacity and capabilities to inform future investments or the implementation of NAPs for AMR.
Keywords: Health systems evaluation; Infections, diseases, disorders, injuries; Medical microbiology; Public Health; Animals; Humans; Anti-Bacterial Agents; Drug Resistance, Bacterial; Anti-Infective Agents; Policy; Capacity Building